PENGARUH KEPUTUSAN PEMBELIAN TERHADAP KINERJA BISNIS INDUSTRI PUPUK ORGANIK - Ramli, Yanto (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose– The purpose of this study is to analyze the influence of market attractiveness, unique resources, and decision to buy towards the business performance of the organic fertilizer industries in Indonesia. Methodology –The research method used is in this research is a descriptive method using scoring analysis and verification method by using quantitative analysis. The determination of the sample is done through Simple Random Sampling because the organic fertilizer industries have the same characteristic, and the analysis tool used is Partial Least Square (PLS). Findings– The results of this study indicate that the unique resources have a significant influence compare to market attractiveness against business performance through the intervening variables of the decision to buy. The decision to buy also has a significant influence on business performance because market attractiveness and unique resources need to obtain the decision to buy from consumers in order to produce good business performance. Implications –Thus, the understanding of the needs and wants of consumers and continuing to develop company resources is something that can improve the business performance of the organic fertilizer industries in Indonesia.Keywords: Market attractiveness, Unique resources, Decision to buy, Business performance